Efficacy of branched chain amino acids supplementation in liver cirrhosis: A systematic review and meta-analysis. Issue 6 (June 2022) - Konstantis, Georgios; Pourzitaki, Chryssa; Chourdakis, Michail; Kitsikidou, Elisavet; Germanidis, Georgios
Summary: Background: Branched chain amino acids' (BCAAs) beneficial role in the management of hepatic encephalopathy is already well established, whereas a number of randomized clinical trials (RCTs) have showed promising results examining BCAA supplementation in the management of other aspects of liver cirrhosis. Current results in the light of BCAAs' biochemical properties make them an attractive supplementation option, in addition to standard pharmaceutical treatment of cirrhosis. Aim: The aim of this systematic review is to summarize the current literature and assess the efficacy of BCAA supplementation in patients with liver cirrhosis. Methods: Major electronic databases and grey literature sources were searched up to October 4th, 2021 for RCTs assessing the supplementation of BCAA against an active comparator, diet or placebo in patients with liver cirrhosis. Results: Twenty RCTs fulfilled selection criteria. Relative to other interventions BCAAs showed beneficial effect regarding muscle mass (SMD 0.21, 95% CI 0.01 to 0.4, I 2 0%), but no effect regarding fat mass. Furthermore, BCAAs were associated with significant increase in plasma albumin concentration (SMD 0.52, CI 95% 0.18 to 0.86, I 2 84.99%), reduction in occurrence of serious cirrhotic complications (logOR −046, CI 95% −0.78 to −0.13, I 2 0%) and increase in body mass index (WMD 0.24, CI 95% 0.08 to 0.40, I 2 0%). On the other hand, no significant effect was noted concerning the incidence of mortality. Conclusion: Supplementation with BCAA seems to improve significant prognostic factors for patients with cirrhosis, with potential positive impact in mortality. Heterogeneity of study findings attributed to many factors limit overall conclusion and results require further assessment.